Leaf anatomy and macro-morphology uncover a new species of Amorimia (Malpighiaceae) from Southeastern Brazil - Almeida, Rafael Felipe De; Mello, Ana Caroline Marques Pereira; Oliveira, Denise Maria Trombert; Amorim, André Marcio Araújo (Phytotaxa, 2017)
The description of a new species belonging to the Amorimia rigida complex (Malpighiaceae) is herein presented, based on leaf anatomy and macro-morphology. Amorimia tumida is endemic to northern state of Rio de Janeiro, Brazil, and it can be differentiated from the remaining species of the A. rigida complex by the absence of glands on the leaf blades, elliptic leaf blades, divergent angle of the secondary veins, reduced number of flowers in the inflorescence, thickened fruiting pedicels, and indumentum of the filaments, styles and samaras. This study includes macro and micro-morphological descriptions, along with an updated identification key for the species of the complex, illustrations, a distribution map, conservation assessment, and comments on ecology and taxonomy.